Influence of mechanical stress in a packaged frequency-modulated MEMS accelerometer - Moreira, Eurico Esteves (2020)
Frequency modulated accelerometers composed of two double-ended tuning fork (DETF) resonators on a differential configuration were characterized for their sensitivity to force applied to their package. Commonly, differential architectures are employed to cancel common mode errors, such as the mechanical stress or temperature dependency. The device dependence to mechanical stress was experimentally measured for forces up to 15 N and a reduction of about 5.6 times was obtained on the differential measurement. Additionally, the silicon dies were glued to chip-carriers using two different glues with distinct properties, and their sensitivity to stress was compared. The effectiveness of a viscoelastic glue over an epoxy-based glue for stress decoupling was tested. Long-term measurements under constant force were experimentally performed and for a time period of approximately 100 min, the stress relaxation and creeping of the viscoelastic glue enabled the recovery to the initial output of the sensor.